Tinjauan Yuridis Penyelesaian Kredit Macet Pembiayaan Syari’ah Model Ijarah Muntahiya Bittamlik dengan Hak Tanggungan di Badan Urusan Piutang Lelang Negara (Studi Putusan Pengadilan Agama Nomor: 554/PDT.G/2018/PA.Pal) - Vini Fitriani; Rohmad Adi Yulianto; Fauziah Fauziah (Jurnal Hukum Jurisdictie, 2021)
Sharia Bank is an Islamic bank that is starting to be in great demand by Indonesians, especially Muslims. Financing. In the running of the IMBT contract, bad credit problems often occur by the customer to the bank with guarantees of security rights to pay off their obligations. Usually the bank will ask the Head of the Religious Court to carry out the execution. When there is no good faith from the customer to the bank, the bank asks the Head of the Religious Court to submit a written auction request to (KPKNL) to sell auction of goods that have been executed. In this paper, the author focuses on the formulation of the problem, namely: 1. How is the IMBT model of shari'ah financing mechanism with guarantees of mortgage rights? auction implementation of the mortgage rights of Ijarah Muntahiya Bittamlik syari'ah financing with guarantees of coverage rights at BUPLN?